GPSR-TARS: congestion aware geographically targeted remote surveillance for VANETs - Walker, Adam; Radenkovic, Milena (2017)
Video over vehicular networks continues to receive warranted attention, with envisioned applications having the potential to present entirely new opportunities and revolutionise existing services. Many video systems have been proposed, ranging from safety to advertising. We propose a novel system for VANETs, namely the TArgeted Remote Surveillance (TARS) module for the existing Greedy Perimeter Stateless Routing (GPSR) protocol which permits multiple mobile vehicles to request and receive live video feeds from vehicles within a select geographic region. The multi-hop, vehicle-to-vehicle system enables mobile units to surveil a target area in real time by leveraging the dashboard cameras of vehicles moving within the target region. We combine several proposed extensions to the core protocol to introduce a dynamic real time congestion aware clustering scheme to achieve this. Our proposed system is compared against existing routing protocols using mobility data from Nottingham. GPSR-TARS outperforms the protocols assessed in key criteria crucial for meeting the quality of service demands of live multimedia dissemination.